Spectrophotometric Determination of Citalopram in Pharmaceutical Formulations - Vidya Sagar, G. (Asian Journal of Chemistry, 2016)
A simple UV spectrophotometric method for the analysis of citalopram either in pure form or in pharmaceutical formulations has been developed. The drug was dissolved in methanol to get a clear solution having λmax 240 nm. The method obeys Beer's law in the concentration range 4–40 μg/mL.